Implementasi Metode Scrum dalam Pengembangan Sistem Informasi Sarana dan Prasarana Sekolah - Hasypa Aulia; Muhammad Dedi Irawan (Teknik Informatika Fakultas Ilmu Komputer, 2025)
This research aims to develop a School Facilities Information System (SISAPRAS) using the Scrum methodology to enhance the efficiency of school facilities management. The Scrum method was chosen for its ability to manage the development process iteratively and collaboratively, involving daily scrum meetings, Sprint Reviews, and Sprint Retrospectives to monitor and adjust team tasks. Blackbox testing was applied to ensure that features like login, dashboard, profile accounts, item reports, and CRUD functions met user requirements. The results indicate that implementing the Scrum methodology in developing SISAPRAS improves efficiency, quality, and timeliness in task completion, as well as allows for quick adaptation to changes and user needs. Consequently, the resulting system effectively provides solutions for managing school facilities.